2019
DOI: 10.1002/lom3.10307
|View full text |Cite
|
Sign up to set email alerts
|

A new numerical model for understanding free and dissolved gas progression toward the atmosphere in aquatic methane seepage systems

Abstract: We present a marine two‐phase gas model in one dimension (M2PG1) resolving interaction between the free and dissolved gas phases and the gas propagation toward the atmosphere in aquatic environments. The motivation for the model development was to improve the understanding of benthic methane seepage impact on aquatic environments and its effect on atmospheric greenhouse gas composition. Rising, dissolution, and exsolution of a wide size‐range of bubbles comprising several gas species are modeled simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…We observed high CH4 concentrations up to 75-100 masf, which is in agreement with bubble models (e.g. McGinnis et al, 2006;Jansson et al, 2019), highlighting that bubbles of observed sizes (~3 mm average equivalent radius) are fully dissolved within this range. Density stratification plays an important role in the vertical distribution of dissolved CH4 because turbulent energy is required to mix solvents across isopycnals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed high CH4 concentrations up to 75-100 masf, which is in agreement with bubble models (e.g. McGinnis et al, 2006;Jansson et al, 2019), highlighting that bubbles of observed sizes (~3 mm average equivalent radius) are fully dissolved within this range. Density stratification plays an important role in the vertical distribution of dissolved CH4 because turbulent energy is required to mix solvents across isopycnals.…”
Section: Discussionsupporting
confidence: 90%
“…1a. FlareHunter derived flow rates within 50 m from line 3 were projected into the model domain, and the source of 175 dissolved CH4, mediated by bubbles, was distributed vertically by applying a non-dimensional source-function similar to the approach of Jansson et al (2019): 0( ) = 6.6 × 10 −2 × −0.066× , where z is the vertical distance from the seafloor in metres.…”
Section: Two-dimensional Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…MOx was 10 times more efficient at SP (rate constant k MOx 6 × 10 −3 day −1 ) than in PKF (k MOx 6 × 10 −4 ay −1 ), presumably due to the difference in the hydrography or the size of methanotrophic community. At SP, a well-defined pycnocline ( Figure 4A SP-3 panel) hindered the transport of gas bubbles to upper layers (Damm et al, 2005;Damm et al, 2008;Gentz et al, 2014;Jansson et al, 2019) whereas the vertical transport of methane was easier in uniform and shallow water column at PKF ( Figure 4A PKF-2 panel).…”
Section: Effect Of Hydrography On Methane Concentrations and Methane mentioning
confidence: 99%
“…Seeping gases form bubbles and rise up through the water column (Westbrook et al, 2009;Berndt et al, 2014). Along its trajectory towards the upper layers, methane exchanges with more abundant dissolved gases such as nitrogen, enriched in the surrounding water and promotes MOx (James et al, 2016;Steinle et al, 2016;Jansson et al, 2019). Hydroacoustic surveys demonstrated that seeps can stay active for weeks to decades (Gentz et al, 2014;Veloso-Alarcón et al, 2019) however, the fate of methane at active flares sites is highly dependent on bubble size, salinity, and water velocity (Jansson et al, 2019).…”
Section: Do Cold Seeps Alter Dissolved Organic Matter Composition?mentioning
confidence: 99%